Assessing Students’ Mathematical Literacy through PISA Items in the Space and Shape Content - Inaara Pangesti Marsyandia; Duano Sapta Nusantara; Tria Gustiningsi (Brillo Journal, 2025)
This study aims to analyze students’ mathematical literacy in solving PISA problems, particularly in the space and shape domain. The research approach used is a qualitative approach. This type of research is qualitative descriptive approach. The study involved 27 ninth-grade students from one of Junior High School (JHS) in Kota Jambi. Data were collected through a written test using items adopted from the 2012 PISA Mathematics Released Problems, complemented by interviews to gain deeper insights. The results revealed that students’ mathematical literacy abilities were categorized into high, medium, and low levels. The results show that most students demonstrate low mathematical literacy skills. Based on the three indicators of mathematical literacy, students in the high-ability category were able to formulate mathematical models, employ geometric concepts appropriately, and interpret the results within the given context. Students in the medium category were able to perform correct procedures but were unable to derive meaningful conclusions, while students in the low category experienced difficulties in all indicators. These findings indicate that students’ mathematical literacy skills in geometry remain limited, particularly in reasoning and interpreting results. Therefore, learning activities that facilitate reasoning and provide more PISA-like tasks are needed to help strengthen students’ mathematical literacy, especially in space and shape problems. Future research may also explore the use of locally contextualized PISA-like tasks to provide students with more meaningful and relatable problem situations.